Video Capsule Retention in Inflammatory Bowel Disease: An Unusual Presentation and Discussion of Retrieval Methods. (3rd March 2013) - Goel, R.; Hardman, J.; Gulati, M.; O'Donohue, J.
Abstract : Inflammatory Bowel Disease (IBD) is characterized by chronic inflammation in the gastrointestinal (GI) tract. Video capsule endoscopy (VCE) is widely used to investigate the small bowel, and capsule retention is the most serious potential complication. Endoscopic and surgical management has been reported, but in the absence of bowel obstruction, there is little consensus as to which should be employed. In this case report, we describe a patient who was investigated with VCE for weight loss and anaemia. He had previously undergone colectomy with ileoanal pouch formation for ulcerative colitis (UC). Capsule retention occurred at an ileal stricture and he was subsequently diagnosed with Crohn's disease (CD). We describe his medical management and successful capsule retrieval using endoscopic methods. This case also highlights the importance of screening for intestinal strictures in an atypical presentation of UC following colectomy.